Hypoadiponectinemia: A Link between Visceral Obesity and Metabolic Syndrome - Tiziana Di Chiara; Christiano Argano; Salvatore Corrao; Rosario Scaglione; Giuseppe Licata (Journal of Nutrition and Metabolism)
Metabolic syndrome (MetS) represents a combination of cardiometabolic risk factors, including visceral obesity, glucose intolerance or type 2 diabetes, elevated triglycerides, reduced HDL cholesterol, and hypertension. MetS is rapidly increasing in prevalence worldwide as a consequence of the “epidemic” obesity, with a considerable impact on the global incidence of cardiovascular disease and type 2 diabetes. At present, there is a growing interest on the role of visceral fat accumulation in the occurrence of MetS. In this review, the effects of adipocytokines and other proinflammatory factors produced by fat accumulation on the occurrence of the MetS have been also emphasized. Accordingly, the “hypoadiponectinemia” has been proposed as the most interesting new hypothesis to explain the pathophysiology of MetS.